Hospitality industry careers: Analysis on students interest based on different location of upbringing and secondary school background / Mohd Salehuddin Mohd Zahari, Fadzillah Mohd Shariff and Tuan Ahmad Tuan Ismail - Mohd Zahari, Mohd Salehuddin; Mohd Shariff, Fadzillah; Tuan Ismail, Tuan Ahmad (2014)
This study investigated the relationships between the geographical location of upbringing, type of secondary schools attended and attitudes and motivation of Malaysian hospitality students towards a hospitality career. A sample of students (year1, 2 and 3) of Diploma Culinary Arts, Hotel Management and Food Service Management from Faculty of Hotel and Tourism Management, MARA University of Technology, Malaysia (Shah Alam, Dungun and Penang campuses) were used in this study. A total 469 usable questionnaires were collected comprises of 173 of year -one, 161 by year- two and 135 of year three. Despite no sustained impact on the perceptions or expectations of hospitality students through the program, there are some distinct differences at the start of their tertiary program between students from different types of secondary schooling and areas of upbringing. Students from rural areas identify themselves of having unclear idea and less knowledgeable about the program and industry at the time of making their career choice as compared to those from towns and cities. Similarly, students from normal secondary school backgrounds also classify themselves as less informed, having more unrealistic perceptions and views about the industry than those from vocational schools. It is recommended that career guidance and orientation should be made more effective, especially for the normal secondary schools to ensure students are informed realistically and sufficiently about careers and working conditions in the hospitality industry. Developing more realistic and lower expectations about working in the industry will allow young people to choose to study in a hospitality program based on a considered career decision rather than by a chance matching of personal needs with what the industry has to offer. In addition, there is a need to educate parents, as well as young people, in the rural areas about these career options and vocational education should be more highly promoted to the rural youth.